FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN ORANG TUA MENYEKOLAHKAN ANAKNYA DI SDS GOLDEN CHRISTIAN SCHOOL - Windra, Windra; Pradiani, Theresia; Fathorrahman, Fathorrahman (Parsimonia - Jurnal Ekonomi dan Bisnis, 2025)
The quality of education is a crucial aspect that must be achieved to face the challenges of competition among educational institutions. One of the strategies for organizations, particularly education institutions focusing on quality, is by implementing quality assurance. Once quality assurance is achieved, educational institutions will continuously improve the quality of services provided to parents, including tangible, reliability, responsiveness, assurance, and empathy. This research aims to analyze the phenomena related to tangible, reliability, responsiveness, assurance, and empathy concerning parents' satisfaction at SDS Golden Christian School. The study population includes the parents of students at SDS Golden Christian School during the 2024-2025 academic year. The sampling technique used is purposive sampling, with questionnaires distributed to 52 respondents who are parents with more than one child enrolled at SDS Golden Christian School in the 2024-2025 academic year. The research data were processed quantitatively using multiple linear regression analysis with validity tests, reliability tests, classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), and hypothesis tests (R² test, t-test, and F-test) utilizing SPSS 30 for Windows. The findings of this research indicate that: 1) Tangible has a positive and significant influence on Parents' Satisfaction. 2) Reliability has a positive but not significant influence on Parents' Satisfaction. 3) Responsiveness has a positive but not significant influence on Parents' Satisfaction. 4) Assurance has a positive but not significant influence on Parents' Satisfaction. 5) Empathy has a positive and significant influence on Parents' Satisfaction. 6) Tangible, reliability, responsiveness, assurance, and empathy collectively have a positive and significant influence on Parents' Satisfaction.